Intercultural communication : a contextual approach - Neuliep, James William ([Place of publication not identifed] : [publisher not identified], 2018)
This book is designed for undergraduate students taking their first course in intercultural communication. The purpose of the book is to introduce the students to the fundamental topics, theories, concepts and themes at the center of the study of intercultural communication.
Chapter1. The necessity of intercultural communication -- Chapter2. The cultural context -- Chapter3. The microcultural context -- Chapter4. The environmental context -- Chapter5. The perceptual context -- Chapter6. The sociorelational context -- Chapter7. The verbal code -- Chapter8. The nonverbal code -- Chapter9. Developing intercultural relationship -- Chapter10. Intercultural conflict -- Chapter11. Intercultural communication in business, healthcare and educational setting -- Chapter12. Acculturation, culture shock and intercultural competence .
Includes bibliographical references and index.
Keywords: INTERCULTURAL COMMUNICATION